Budaya manajemen risiko: Mendorong kesadaran dan komitmen seluruh pemangku kepentingan - Arfyansya, Moh Arya (Maliki Interdisciplinary Journal, 2024)
Risk management culture has become an important aspect of ensuring organizational success in the modern era, where uncertainty and rapid change are commonplace. This research explores the importance of risk management culture in modern organizations, focusing on how awareness and commitment of all stakeholders can drive effective risk management. Through a literature review, key factors discussed include strong leadership, employee engagement, open risk communication, and the use of modern technology to support risk identification and mitigation. The results show that an effective risk management culture requires proactive leadership and consistent engagement from all stakeholders. The research confirms that a strong risk management culture contributes to organizational stability and sustainability. With a comprehensive approach that includes engagement, communication, and technology, organizations can build a culture that allows them to thrive in the face of risk and uncertainty